2018
DOI: 10.1016/j.jtho.2018.08.308
|View full text |Cite
|
Sign up to set email alerts
|

OA13.03 Anlotinib as Third-Line or Further-Line Treatment in Relapsed SCLC: A Multicentre, Randomized, Double-Blind Phase 2 Trial

Abstract: Background: The role of 18 fludeoxyglucose ( 18 F-FDG) PET/CT in the management of limited stage small-cell lung cancer (LS-SCLC) is uncertain. Previous studies have shown that 18 F-FDG PET/CT upstages up to 30% of LS-SCLC patients. Data from the CONVERT trial was analysed to investigate the impact of 18 F-FDG PET/CT in the management of LS-SCLC. The prognostic significance of pre-treatment 18 F-FDG PET parameters was also investigated in an exploratory analysis. Method: CONVERT is an international multi-centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 0 publications
4
56
1
Order By: Relevance
“…The observed toxicity profile in this study was similar to a previous study of anlotinib in NSCLC. G 3–4 toxicity was slightly higher than in the placebo group with on target toxicity of bleeding in the form of hemoptysis being the most serious complication observed on the study, which occurred in four patients with only one case requiring treatment intervention [61].…”
Section: Targeted Therapymentioning
confidence: 99%
“…The observed toxicity profile in this study was similar to a previous study of anlotinib in NSCLC. G 3–4 toxicity was slightly higher than in the placebo group with on target toxicity of bleeding in the form of hemoptysis being the most serious complication observed on the study, which occurred in four patients with only one case requiring treatment intervention [61].…”
Section: Targeted Therapymentioning
confidence: 99%
“…Regarding the efficacy of anlotinib in SCLC, another multicenter, randomized, double-blind phase II trial was performed. Cheng et al (38) investigated anlotinib vs. placebo for the third-or further-line treatment of SCLC (ALTER1202, NCT03059797). In the trial, 120 enrolled patients with limited-or extensive-stage SCLC who failed at least 2 lines of chemotherapy were randomized at a 2:1 ratio to the anlotinib arm or placebo arm (12 mg per os QD from day 1 to 14, every 3 weeks).…”
Section: Clinical Trials Of Anlotinibmentioning
confidence: 99%
“…However, it is also associated with various AEs that may affect the QoL of patients and hinder patient compliance to treatment. Studies have indicated that the percentage of AEs (all grades) that occurred in anlotinib-treated patients was 87.70-100%, and grade 3 or higher AEs were reported in 21.67-61.90% of anlotinib-treated patients (34,37,38,62,65), and the percentages differed among the clinical trials. The most common AEs associated with anlotinib treatment included hypertension, HFSR, fatigue, diarrhea and anorexia.…”
Section: Management Of Drug-associated Aesmentioning
confidence: 99%
“…In view of excellent outcomes in the ALTER 1202 trial, the use of anlotinib as third-line and further-line therapy or maintenance therapy to prolong PFS was approved by the CSCO in China to treat SCLC. [15] However, results of the use of immune checkpoint inhibitors in SCLC seem disappointing. Nevertheless, research is ongoing.…”
Section: Discussionmentioning
confidence: 99%